(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
This paper deals with the research on simulation design of traditional Chinese costumes in digital method. We take Chi-pao (Cheongsam), the Mandarin gown of the Qing Dynasty as the research object and conduct a comprehensive analysis of its structures, colors, patterns and other traditional crafts. Then a simulation digital design is made and cutting pieces are printed through digital printer. The finished product shows that the simulation of traditional costumes through this method is feasible to achieve satisfactory results. Thus, simulation design can be used as one of the ways to research, inherit and spread the traditional Chinese costumes.